2007
DOI: 10.1080/01485010600889134
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Levels of Estradiol and Testosterone in Seminal Plasma andGSTM1Polymorphism in Infertile Men

Abstract: Glutathione S-transferase M1 (GSTM1) enzyme serves as a steroid-binding protein by its ability to bind to testosterone and estradiol. The levels of total estradiol and testosterone were measured by using an electrochemiluminescence immunoassay in serum and seminal plasma from 103 subjects including 62 subfertile patients. GSTM1 polymorphism was examined using polymerase chain reaction. The estradiol and testosterone levels in seminal plasma were not different in control and subfertile subjects. No role for GST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In stallions, seminal plasma CRISP3 was positively related to first-cycle conception rate and may be a good marker of fertility [1]. However, male infertility in Nigerians is characterized by raised seminal plasma testosterone [56], and there was no difference in testosterone levels in seminal plasma in fertile and subfertile men [57]. In this study, serum analysis showed higher GPx activity and elevated concentrations of sPLA 2 , CRISP3, and testosterone and lower levels of MDA, IGF-1, and clusterin in the fertile dromedaries in comparison with the infertile group.…”
Section: Biomarkersmentioning
confidence: 99%
“…In stallions, seminal plasma CRISP3 was positively related to first-cycle conception rate and may be a good marker of fertility [1]. However, male infertility in Nigerians is characterized by raised seminal plasma testosterone [56], and there was no difference in testosterone levels in seminal plasma in fertile and subfertile men [57]. In this study, serum analysis showed higher GPx activity and elevated concentrations of sPLA 2 , CRISP3, and testosterone and lower levels of MDA, IGF-1, and clusterin in the fertile dromedaries in comparison with the infertile group.…”
Section: Biomarkersmentioning
confidence: 99%
“…GSTM proteins are steroid binding proteins characterized by their properties to bind testosterone and estradiol [53]. Upregulation of these antioxidant proteins has been related to drug insult, and detoxification of xenobiotics and oxidative products [54].…”
Section: Discussionmentioning
confidence: 99%
“…However, candidate gene studies are often non-reproducible, because the effects of candidate markers are specific for some populations (Georges 2007). In addition, 43 candidate genes showed positive association between DNA sequence variation (base substitutions, indels, the number of trinucleotide repeats) and human male infertility phenotypes (Fritsche et al 1998;Holyoake et al 1999;Ramanujam et al 2000;van der Ven et al 2000;Kucera et al 2001;Rovio et al 2001;Pan et al 2002;Teng et al 2002;Tsujimura et al 2002;Maiorino et al 2003;Tanaka et al 2003;Jensen et al 2004;Watanabe et al 2004;Westerveld et al 2004;Ahda et al 2005;Galan et al 2005;Miyagawa et al 2005;Paduch et al 2005;Stouffs et al 2005;Vouk et al 2005;Aoki et al 2006;Christensen et al 2006;Galan et al 2006;Lee et al 2006;Peterlin et al 2006;Rani et al 2006;Sato et al 2006;Tsujimura et al 2006;Westerveld et al 2006;Zhoucun et al 2006a,b;Bonache et al 2007;Dhillon et al 2007;Lu et al 2007;Onaran et al 2007;Ravel et al 2007;Tu¨ttelmann et al 2007;Gunel-Ozcan et al 2008;…”
Section: Association Studiesmentioning
confidence: 99%